Working-class youth professional choices: option or legitimation (Research, Society and Development, 2020)
The professional choice is usually made in a reflection in which is necessary to take into account issues as contradiction, class struggle and the search for means of survival. When it comes to the scenario of the discussion, working-class young people, as subjects who make their choices for which professional paths to follow, should not forget that these paths conceive and design their existence in a context. Due to it, the conditions between this or that horizon are limited by the imposition of a historical situation of subjugation and, necessarily, there is a subjection to the order that regulates the social context, benefiting a minority holder of means of production. Thus, it was observed, in this study in which the objective is to trace a parallel between the option that occurs in a context of unrestricted and amplitude and the legitimation of working-class professional choices, that, historically, for part of the population, what is called possibility enters the social environment of the proletariat as a recent policy. During the years, there have been other paths in which the professionalization of the young workers was the opposite of their option, which legitimizes the timeless inequality that is established among the few wealthier and those who need to sell their labor power to earn a living, conditioning a moment of choice to guarantee a swift entry into the labor market. Thus, it is difficult to break the situation of oppression to which young workers are submitted.